Pemanfaatan Grup Whatapps Pada Komunitas Kelas Menulis Pustakawan (KMP) - Indah Wijaya Antasari; Wiwik Novianti (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2019)
This study aims to determine the utilization of WA Group in the KMP community.Whatsapp comes as a new media that serves to communicate between application users. Whatsapp has facilities to create groups where each member can communicate with each other. This study uses a descriptive qualitative approach, with the technique of retrieving data through online observation and interviews. The result is the use of whatsapp groups in the KMP community is quite high / active. The Librarian Writing Class Community, established in 2015 with the aim of sharing through writing, has published six (6) anthology titles, which are: Proud to be librarians, librarians and book meanings, librarians personal brand, library service innovation and hoaxes, building phenomena librarian professional competence, and my inspiration in the library. KMP has also carried out collaborative activities in the field of librarianship and writing.